ANALYSIS OF THE LEARNING PROCESS IN THE SEWING COURSE PROGRAM AT LPK MODES NOOR SAMARINDA - Aisyah Ramadhani; Muhamad Alisalman; Hepy Tri Winarti; Mustangin (SOSIOEDUKASI, 2025)
This study aims to analyze the learning process in the sewing course program at LPK Modes Noor Samarinda. The focus of the research lies in the three main stages of the learning process, namely planning, implementation, and evaluation. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and document studies of instructors and students. The results of the study show that the learning process is designed systematically and adaptively to the diverse backgrounds of students. The planning phase includes setting clear learning objectives, inclusive participant recruitment, selecting competent instructors, providing adequate facilities and infrastructure, and allocated funding to support the sustainability of the program. The implementation stage is carried out in a flexible time with individual material delivery, the use of appropriate learning media, the application of lecture methods, questions and answers, demonstrations, and practices, as well as two-way communication and motivation so as to create a supportive and productive learning atmosphere. Evaluation is carried out formatively and summatively to measure the cognitive, psychomotor, and affective aspects of students. This program shows success in the form of increasing students' knowledge and skills, creating economic opportunities through independent sewing businesses, optimizing free time productively, and changing people's mindset towards the role of women. Overall, the structured and adaptive learning process at LPK Modes Noor makes a real contribution to individual empowerment and community development.